Blood-brain barrier disruption during spontaneous canine visceral leishmaniasis - Melo, G. D. [UNESP]; Grano, F. G. [UNESP]; Silva, J. E.S. [UNESP]; Kremer, B. E. [UNESP]; Lima, V. M.F. [UNESP]; Machado, G. F. [UNESP] (Wiley, 2015)
Visceral leishmaniasis is a complex disease caused by Leishmania infantum, and in dogs, besides the classical symptoms, there are descriptions of inflammatory alterations in the brain. Brain inflammation is a strictly controlled process, and as the brain counts on the efficiency of the blood-brain barrier (BBB), we aimed to assess BBB integrity in dogs with spontaneous visceral leishmaniasis. Therefore, we evaluated markers in the cerebrospinal fluid (CSF) and in brain tissue related to BBB disruption and brain inflammation. Elevated albumin quota revealed BBB breakdown, corroborated by increased concentrations of anti-Leishmania antibodies in the CSF. In the brain, albumin and IgG staining formed halos around blood vessels, a classical indicator of BBB leakage. Soluble IgG was also detected in the choroid plexus and ependyma, and in these structures, IgG stained random resident cells. IgG+ cells and Fcγ-RI+ cells were identified in the choroid plexus, ependyma and perivascular in the brain parenchyma. The data support the occurrence of BBB disruption in dogs with spontaneous visceral leishmaniasis, and IgG as a key molecule that is capable of initiating and/or maintaining the inflammatory stimuli in the nervous milieu and the CSF as an important disseminator of inflammatory stimuli within the CNS.
Keywords: Albumin quota; Central nervous system; Cerebrospinal fluid; Choroid plexus; Fc gamma receptors; Immunoglobulin G